2020
DOI: 10.1021/acscatal.0c03602
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Templating Increases the Catalytic Rate of an Amylase, Maltase, and Glucokinase Multienzyme Cascade through Substrate Channeling Independent of Surface Curvature

Abstract: The templating of enzymes has shown myriad advantages, including increased stability and kinetic rates. Specifically, the use of nanoparticles (NPs) as templates has been shown to increase the kinetic rates over larger macroscale scaffolds, in part by overcoming diffusion limitations. Within the field, there is considerable debate over the parameters that optimize this interaction, e.g., NP size, curvature, and surface ligands. Recently much interest has been seen in the pursuit of complete enzyme cascades on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Kinetic descriptors for each enzyme, both on/off NP include maximum velocity ( V max ), the Michaelis constant ( K M ), catalytic rate ( k cat ), enzyme efficiency ( k cat / K M ), and specific activity (SA) are found in Table 2 21 . Kinetic values are termed “apparent” since it is uncertain if enzyme activity when it is displayed on a NP satisfies all classical Michaelis–Menten (MM) assumptions; nevertheless, they still serve as excellent comparators of activity in the different configurations 37 , 43 , 53 , 54 , 74 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic descriptors for each enzyme, both on/off NP include maximum velocity ( V max ), the Michaelis constant ( K M ), catalytic rate ( k cat ), enzyme efficiency ( k cat / K M ), and specific activity (SA) are found in Table 2 21 . Kinetic values are termed “apparent” since it is uncertain if enzyme activity when it is displayed on a NP satisfies all classical Michaelis–Menten (MM) assumptions; nevertheless, they still serve as excellent comparators of activity in the different configurations 37 , 43 , 53 , 54 , 74 .…”
Section: Resultsmentioning
confidence: 99%
“…Genes for α-amylase from B. cereus , alpha-glucosidase from Saccharomyces pombe which we refer to as maltase 43 , 51 , and INVB an invertase from Zymomonas mobilis 127 , were codon optimized for expression in E. coli and synthesized by Genscript (protein sequences are listed in the Supplementary Materials ). Genes were subsequently cloned into the NcoI and XhoI restriction sites in expression vector pET28a (Addgene).…”
Section: Methodsmentioning
confidence: 99%
“…[94] Recently, Diaz et al showed that the gold templating enhanced the catalytic rate of amylase, maltase and glucokinase multienzyme cascade by~3-fold as compared to the enzymes bound separately and combined freely in solution. [95] Thus, it was evident that the enhanced enzyme kinetics was achieved through substrate channeling. Importantly, the evaluation of enzyme cascade on Au nanoscaffolds of different size and shape revealed the equivalent enhanced multienzyme kinetics suggesting substrate channeling independent of surface curvature.…”
Section: Cascade Reactions In Multienzymatic Gold Nanoparticlesmentioning
confidence: 99%
“…Protein−gold nanoparticle conjugates are poised to play a critical role in next-generation biomedical technologies. 1−7 Advances in diagnostic testing, 8−15 tissue and cellular imaging, 16−18 photothermal therapy, 19 biocatalysis, 20 and drug delivery 21 have been achieved with the integration of functionalized gold nanoparticles. The overall success and widespread implementation of these nanoparticle-enabled technologies hinges on the effectiveness of the protein− nanoparticle conjugate, specifically the interfacial chemistry to immobilize the surface protein.…”
Section: ■ Introductionmentioning
confidence: 99%